Secretory RAB GTPase 3C modulates IL6-STAT3 pathway to promote colon cancer metastasis and is associated with poor prognosis - Yu‐Chan Chang; Chia‐Yi Su; Ming‐Huang Chen; Wei-Shone Chen; Chi‐Long Chen; Michael Hsiao (2017)
RAB GTPases are important in the regulation of membrane trafficking and cell movement. Recently, exocytic RABs have received increasing attention in cancer research. However, the functional roles of exocytic RABs in colorectal carcinogenesis remain to be elucidated. Immunohistochemistry analysis of a microarray containing 215 colorectal adenocarcinoma tissues was used to identify the association between exocytic RABs and patient prognosis. Complementary functional RAB3C overexpression and knockdown experiments were performed. The molecular mechanism of RAB3C in inducing colon cancer cell metastasis was determined. High RAB3C expression in patients was found to be significantly associated with advanced pathological stage, distant metastasis and poor prognosis. Multivariate analyses showed that high RAB3C expression was an independent prognostic marker in overall (P = 0.001) and disease-free survival (P < 0.001). Furthermore, our experimental results showed an increase in the migration and invasion ability of RAB3C-overexpressing colon cancer cells and increased metastatic nodules in a mouse metastasis model. The effect of RAB3C-overexpressing cell-conditioned medium was found to significantly promote the migration ability of parental colon cancer cells, thus suggesting that the promotion of migration is exocytosis dependent. Upregulation of other exocytic RABs was also seen in RAB3C-overexpressing cells. Through microarray and proteomics analyses, increased production of multiple cytokines was observed in RAB3C-overexpressing cell lines, and the IL-6 pathway was the top pathway whose members exhibited gene expression changes after RAB3C overexpression, according to Ingenuity Pathway Analysis. Blocking IL-6 with IL-6 antibody treatment or IL-6 knockdown significantly inhibited the migration potential of RAB3C-overexpressing colon cancer cells. In addition, IL-6 was found to induce STAT3 phosphorylation in RAB3C-overexpressing colon cancer cells, thus promoting migration. Ruxolitinib, a JAK2 inhibitor, was found to significantly inhibit RAB3C-induced colon cancer cell migration. Our study revealed that RAB3C overexpression promotes tumor metastasis and is associated with poor prognosis in colorectal cancer, through modulating the ability of cancer cells to release IL-6 through exocytosis and activate the JAK2-STAT3 signaling pathway. These results further suggest that inhibition of STAT3 phosphorylation in the RAB3C-IL-6-STAT3 axis by using Ruxolitinib may be a new therapeutic strategy to combat metastatic colon cancers.